Triostin A Derived Cyclopeptide as Architectural Template for the Alignment of Four Recognition Units - Kotyrba, Ursula M.; Pröpper, Kevin; Sachs, Eike-F.; Myanovska, Anastasiya; Joppe, Tobias; Lissy, Friederike; Sheldrick, George M.; Koszinowski, Konrad; Diederichsen, Ulf (ChemistryOpen (Weinheim), 2014)
The DNA bisintercalator triostin A is structurally based on a disulfide‐bridged depsipeptide scaffold that provides preorganization of two quinoxaline units in 10.5 Å distance. Triostin A analogues are synthesized with nucleobase recognition units replacing the quinoxalines and containing two additional recognition units in between. Thus, four nucleobase recognition units are organized on a rigid template, well suited for DNA double strand interactions. The new tetra‐nucleobase binders are synthesized as aza‐TANDEM derivatives lacking the N‐methylation of triostin A and based on a cyclopeptide backbone. Synthesis of two tetra‐nucleobase aza‐TANDEM derivatives is established, DNA interaction analyzed by microscale thermophoresis, cytotoxic activity studied and a nucleobase sequence dependent self‐aggregation investigated by mass spectrometry. Designed to match! Four nucleobases were attached to the disulfide bridged cyclopeptide scaffold derived from the DNA bisintercalator triostin. The aza‐TANDEM backbone provides organization and alignment of the nucleobases, allowing for application in sequence‐ dependent DNA recognition and molecular architecture.